Cross-talk between ER and HER2 regulates c-MYC-mediated glutamine metabolism in aromatase inhibitor resistant breast cancer cells. Issue 149 (May 2015) - Chen, Zhike; Wang, Yuanzhong; Warden, Charles; Chen, Shiuan
Graphical abstract: Highlights: Aromatase inhibitor (AI) resistant breast cancer cells are addicted to glutamine. Glutamine consumption is independent of estrogen but still requires ER in AI resistant breast cancer cells. c-MYC expression is up-regulated through the cross-talk between ER and HER2 in AI resistant breast cancer cells. Targeting c-MYC-mediated glutamine metabolism inhibits the proliferation of AI resistant breast cancer cells. Abstract: Resistance to endocrine therapies in hormone receptor (HR)-positive breast cancer is a significant clinical problem for a considerable number of patients. The oncogenic transcription factor c-MYC (hereafter referred to as MYC), which regulates glutamine metabolism in cancer cells, has been linked to endocrine resistance. We were interested in whether MYC-mediated glutamine metabolism is also associated with aromatase inhibitor (AI) resistant breast cancer. We studied the expression and regulation of MYC and the effects of inhibition of MYC expression in both AI sensitive and resistant breast cancer cells. Considering the role of MYC in glutamine metabolism, we evaluated the contribution of glutamine to the proliferation of AI sensitive and resistant cells, and performed RNA-sequencing to investigate mechanisms of MYC-mediated glutamine utilization in AI resistance. We found that glutamine metabolism was independent of estrogen but still required estrogen receptor (ER) in AI resistant breast cancer cells. The expression of MYC oncogene was up-regulated through the cross-talk between ER and human epidermal growth factor receptor 2 (HER2) in AI resistant breast cancer cells. Moreover, the glutamine transporter solute carrier family (SLC) 1A5 was significantly up-regulated in AI resistant breast cancer cells. ER down-regulator fulvestrant inhibited MYC, SLC1A5, glutaminase (GLS) and glutamine consumption in AI resistant breast cancer cells. Inhibition of MYC, SLC1A5 and GLS decreased AI resistant breast cancer cell proliferation. Our study has uncovered that MYC expression is up-regulated by the cross-talk between ER and HER2 in AI resistant breast cancer cells. MYC-mediated glutamine metabolism is associated with AI resistance of breast cancer.